2016
DOI: 10.1016/j.jval.2016.09.2390
|View full text |Cite
|
Sign up to set email alerts
|

Real World Anaplastic Lymphoma Kinase (ALK) Rearrangement Testing Patterns, Treatment Sequences and Survival of ALK-Inhibitor Treated Patients

Abstract: The search yielded 350 citations with two additional citations identified through examination of reference lists of the included publications. After applying the selection criteria, six articles that described eight different study cohorts were included in the qualitative data synthesis. Seven study cohorts were retrospective analyses and one was a physician panel survey. Six study cohorts included patients from Europe, and two included patients from the USA. Among studies that followed patients from primary G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…Similar to results from previously conducted studies of real‐world treatment patterns for ALK + NSCLC [25, 26, 36–39], we found that crizotinib was the most commonly prescribed first‐line ALK TKI therapy in clinical practice. In the second‐line ALK TKI setting (post crizotinib), our results showed that ceritinib was the most commonly prescribed therapy, which is consistent with the approval timelines and similar to the results of other real‐world studies [24, 25, 37–42]. These results are not surprising, as crizotinib was initially approved by the FDA in 2011 and was the first commercially available ALK TKI therapy in the U.S. [43].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to results from previously conducted studies of real‐world treatment patterns for ALK + NSCLC [25, 26, 36–39], we found that crizotinib was the most commonly prescribed first‐line ALK TKI therapy in clinical practice. In the second‐line ALK TKI setting (post crizotinib), our results showed that ceritinib was the most commonly prescribed therapy, which is consistent with the approval timelines and similar to the results of other real‐world studies [24, 25, 37–42]. These results are not surprising, as crizotinib was initially approved by the FDA in 2011 and was the first commercially available ALK TKI therapy in the U.S. [43].…”
Section: Discussionsupporting
confidence: 87%
“…We focused on community centers, where the majority of cancer care in this country is provided. Therefore, we believe this study provides a robust view of oncology practice in the real world and continues to advance the current knowledge around ALK testing patterns [21]. However, the standard limitations inherent to retrospective real‐world data studies also apply to this study, such as the potential for coding errors in oncology practices and missing data if procedures or treatments occurred outside the specific oncology practice.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we believe this study provides a robust view of oncology practice in the real-world and continues to advance the current knowledge around ALK testing patterns. 21 However, the standard limitations inherent to retrospective real world data studies also apply to this study, such as the potential for coding errors in oncology practices and missing data if procedures or treatments occurred outside the specific onocology practice. As an example, patients' ALK testing status might not be captured in the database if the testing was performed outside the Flatiron Health network or was not recorded in the EHR system.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have similarly shown an increasing rate of biomarker testing in the US over the past decade. [25][26][27][28][29][30][31][32] In a survey conducted in 2015, 38% of newly diagnosed patients with NSCLC, including 32% of those treated in a community-based center, were tested for ROS1, 20 lower than rates observed from 2016 to 2018 in this study of patients with advanced NSCLC.…”
Section: William Wong Et Almentioning
confidence: 94%